A role for corticosteroid-binding globulin variants in stress-related disorders. Issue 3 (May 2012) - Marathe, Chinmay S; Torpy, David J
Primary stress-related diseases such as chronic fatigue syndrome, fibromyalgia or chronic widespread pain have been associated with altered activity of the hypothalamic–pituitary–adrenal axis due to measured relative hyper- or hypo-cortisolism in basal or experimentally stimulated states. A hereditary risk to development of these diseases has been proposed. Corticosteroid-binding globulin (CBG), a plasma transport vehicle for cortisol, may play a more active role in the hypothalamic–pituitary–adrenal axis. Chronically altered hypothalamic–pituitary–adrenal axis has been associated with common medical problems. Hypocortisolism has been observed in kindred studies of rare mutations of the SERPIN A6 (CBG) gene and more common SERPIN A6 polymorphisms associated with reduced CBG levels or CBG:cortisol-binding affinity. Over the last decade, studies of five different CBG gene mutations in humans, human genetic associations and transgenic mouse models have suggested that CBG may have hitherto unexpected roles in modulation of the stress response. Naturally occurring CBG variants may alter susceptibility to disorders associated with chronic stress and relative hypocortisolism. On the other hand, hypercortisolism has been linked with Cushing's disease and metabolic syndrome and CBG gene polymorphisms have been linked to obesity in animal models. In this article, we look at the evidence suggesting a role for CBG in stress-related disorders, focusing particularly on CBG gene polymorphisms and chronic pain/fatigue syndromes.